Fit-for-discharge criteria after esophagectomy: an International Expert Delphi Consensus - Müller, Philip C.; Kapp, J R; Vetter, D; Bonavina, L; Brown, W; Castro, S; Cheong, E; Darling, G E; Egberts, J; Ferri, L; Gisbertz, S S; Gockel, I; et al. (Diseases of the esophagus, 2021)
There are no internationally recognized criteria available to determine preparedness for hospital discharge after esophagectomy. This study aims to achieve international consensus using Delphi methodology. The expert panel consisted of 40 esophageal surgeons spanning 16 countries and 4 continents. During a 3-round, web-based Delphi process, experts voted for discharge criteria using 5-point Likert scales. Data were analyzed using descriptive statistics. Consensus was reached if agreement was ≥75% in round 3. Consensus was achieved for the following basic criteria: nutritional requirements are met by oral intake of at least liquids with optional supplementary nutrition via jejunal feeding tube. The patient should have passed flatus and does not require oxygen during mobilization or at rest. Central venous catheters should be removed. Adequate analgesia at rest and during mobilization is achieved using both oral opioid and non-opioid analgesics. All vital signs should be normal unless abnormal preoperatively. Inflammatory parameters should be trending down and close to normal (leucocyte count ≤12G/l and C-reactive protein ≤80 mg/dl). This multinational Delphi survey represents the first expert-led process for consensus criteria to determine ‘fit-for-discharge’ status after esophagectomy. Results of this Delphi survey may be applied to clinical outcomes research as an objective measure of short-term recovery. Furthermore, standardized endpoints identified through this process may be used in clinical practice to guide decisions regarding patient discharge and may help to reduce the risk of premature discharge or prolonged admission.